Approaches and Challenges in the Management of Multiple Myeloma in the Very Old: Future Treatment Prospects - Kaweme, Natasha Mupeta; Changwe, Geoffrey Joseph; Zhou, Fuling (Frontiers in Medicine, 2021)
The increasing incidence of geriatric patients with multiple myeloma has elevated concerns in clinical practice. While the introduction of novel therapeutic agents has substantially improved outcomes in younger patients with myeloma, poorer outcomes remain in older patients. Managing older patients requires a multidisciplinary team approach to consider factors that may influence both treatment selection and outcomes. Aging is associated with remodeling of vital organs, physiological downregulations of basal metabolism, susceptibility to multiple comorbidities with ultimate frailty, thereby contributing to the underrepresentation and exclusion of very old patients from clinical trials. Therefore, timely confirmation of a precise diagnosis is crucial for prompt initiation of treatment if the desired outcome is to be achieved. Adequate and judicious assessment using comprehensive geriatric assessment tools minimizes toxicities and treatment discontinuation. Initiating treatment with combinational therapy requires knowledge of indications and anticipated outcomes, as well as individualized therapy with appropriate dose-adjustment. Individualized therapy based on good clinical acumen and best practices obverts unwanted polypharmacy, preventing iatrogenic harm. This review will therefore address the approaches and challenges faced in managing myeloma in geriatric patients aged 80 years and older, highlighting recommended therapeutic strategies and future prospective regimens.